2020
DOI: 10.14778/3384345.3384354
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and benchmarking the impact of GDPR on database systems

Abstract: e General Data Protection Regulation (GDPR) was introduced in Europe to o er new rights and protections to people concerning their personal data. We investigate GDPR from a database systems perspective, translating its legal articles into a set of capabilities and characteristics that compliant systems must support. Our analysis reveals the phenomenon of metadata explosion, wherein large quantities of metadata needs to be stored along with the personal data to satisfy the GDPR requirements. Our analysis also h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Benchmarking approaches from other closely related domains, such as cloud computing, can often be adapted or reused for edge environments. For example, there are large numbers of starting points for elastic scalability (38,60,(145)(146)(147)(148), availability (149)(150)(151)(152)(153)(154)(155), data consistency (45,46,144,(156)(157)(158)(159)(160), and security and privacy (54,(161)(162)(163)(164)(165)(166)(167). A more detailed discussion of additional quality dimensions for edge benchmarking is beyond the scope of this paper.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Benchmarking approaches from other closely related domains, such as cloud computing, can often be adapted or reused for edge environments. For example, there are large numbers of starting points for elastic scalability (38,60,(145)(146)(147)(148), availability (149)(150)(151)(152)(153)(154)(155), data consistency (45,46,144,(156)(157)(158)(159)(160), and security and privacy (54,(161)(162)(163)(164)(165)(166)(167). A more detailed discussion of additional quality dimensions for edge benchmarking is beyond the scope of this paper.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Some recent works start to rethink the system design in the era of the GDPR or measure the cost of compliance. [92] showed that the performance of a GDPR-compliant database will scale poorly as the volume of personal data increases. Frictions between cloud-scale systems and the GDPR has also been discussed [93].…”
Section: Related Workmentioning
confidence: 99%
“…GDPRBench [Shastri et al 2020] is a benchmark suite built upon YCSB and proposes to evaluate the impacts on performance of making a DBMS GDPR compliant. Without any major changes, aiming only to evaluate the impact of fulfilling the requirements, modifications were made to Redis, a key-value storage and PostgreSQL, a relational DBMS.…”
Section: Metadata Explosionmentioning
confidence: 99%
“…GDPR Compliance by construction [Schwarzkopf et al 2019] provides the removal of a user shard as a solution for the delete guarantee, however, while it highlights that the underlying views must be aware of this removal, it does not discuss a mechanism ensuring this awareness. GDPRBench [Shastri et al 2020] evaluates this impact by adding a time-to-live attribute to data, and using a daemon or adding this functionality to the DBMS to periodically probe the data in search of TTL violations, as well as deleting them when needed. [Kraska et al 2019] point out that when an entry is deleted in their system, the surrogate keys become dangling, rendering data access impossible.…”
Section: Delete Guaranteesmentioning
confidence: 99%
See 1 more Smart Citation